TINGKAT PENGETAHUAN DAN SIKAP DENGAN KEPATUHAN DIET HIPERTENSI - Emaus Zulkarnain, Albert; Pratama, Kharisma; Hartono (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Hypertension is one of the most common and most prevalent cardiovascular diseases. Hypertension is known by the general public as "high blood pressure" because this condition indeed indicates high blood pressure. Hypertension is the leading cause of death in the world every year. Hypertension is a condition when the measured systolic pressure is ≥ 140 mmHg or diastolic pressure is ≥ 90 mmHg. Objective: The study aimed to analyze the relationship between the level of knowledge and attitude with adherence to a hypertension diet among patients with hypertension in the working area of Lembah Bawang Public Health Center. Methods: This study is a quantitative study using a correlational analytic method that connects the independent (independent) variable with the dependent variable (dependent). This study uses a cross-sectional approach, in which the research subjects are observed, measured, and collected at the same time using a questionnaire of the knowledge and attitudes of hypertensive patients with hypertension diet compliance. Results: The results of the statistical test using the Spearman test at the α = 0.05 significance level showed that there is a relationship between knowledge and hypertension diet compliance in the Lembah Bawang Public Health Center area (p value 0.029 < 0.05) and there is a relationship between attitude and hypertension diet compliance in the Lembah Bawang Public Health Center area (p value 0.021 < 0.05). Conclusion: Good knowledge and a positive attitude have a positive impact on hypertensive patients in adherence to hypertension diet.